The Mediating Role of Servant Leadership in Predicting Green Management Practices: A Preliminary Study - Hafiz, Nur Kamarul; Alias, Zuraini; Kumarasamy, Morkana Muthu; Mokhtar, Norsyahida (UUM Press, 2024)
Green manufacturing practices (GMP) are promoted by the United Nations through an effort known as Sustainable Development Goals (SDGs), which has been welcomed by Malaysia to address global environmental problems, with manufacturing sectors becoming the primary focus, in line with the National Policy goals to enhance the capacity of the manufacturing sector by 2025. However, Malaysia’s green commitment is less encouraging globally, as most manufacturers are still struggling to implement GMP due to weak leadership, resulting in low acceptance within the organization. Servant leadership is proposed as a mediator to help manufacturers implement GMP effectively, where this leadership is less concerned with the context of green practices in Malaysia. In this paper, the influential factors of GMP implementation will also be identified. A total of 40 factory managers responded to the survey used in a pilot study. The initial results show that the most influential factor is law enforcement, based on mean score, followed by proactive communication and technology advancement. Meanwhile, servant leadership did not mediate the relationships between the business environment and organizational factors, except for individual factors and GMP, as employees are empowered to be creative in their own ways. This study offers new perspectives to manufacturers who intend to maintain their commitment towards GMP